Light rail - Ferbrache, F (Elsevier, 2021)
Light rail describes a range of urban rail transit systems running largely on exclusive rights of way within city centers and between city centers and their suburbs. Light rail is different from, though shares similar characteristics with other transit modes such as buses and heavy rail. Following mid-20th century decline of streetcars, light rail emerged in the 1970s as a response to growing traffic congestion and efforts to draw people and investment back into city centers. Light rail is a leading sustainable transport mode renowned for its high service speed, frequency, safety, and reliability. Light rail is recognized for its potential to facilitate and enhance urban (re)development to boost economic growth and property values. Light rail can help to improve environmental quality and social equity though the latter is a largely neglected part of light rail research.